Development and validation of TLC densitometry method for the determination of Gliclazide in tablet dosage form (International Current Pharmaceutical Journal, 2012)
Some tablet pharmaceutical preparations containing Gliclazide as sole active ingredient, are marked now in Indone-sia. The determination of the component of preparation both qualitatively and quantitatively is important to ensure quality of the product. This research is aimed to develop a TLC method to analyze gliclazide in its single component tablet formulation. Gliclazide were dissolved with chloroform. Gliclazide was chromatographed on silica Gel 60 F254 TLC plate using toluene: ethyl acetate in the ratio of 1:1 (v/v) as mobile phase. Gliclazide showed Rf value of 0.58 and was scanned at 234nm using Camag TLC Scanner 3. This method validation showed a good linearity with correlation coefficient (r) of 0.999 while the coefficient of variation of the regression function (Vx0) = 2.406%. Specificity showed calculation of purity and identity more than 0.99. The limit of detection (LOD) and the limit of quantification (LOQ) of the method was respectively 28.78 and 86.35 ng/spot respectively. The mean absolute recovery of Gliclazide from the simulation  sample was  100.5% ± 0.113 and the method precision was less than  5.3% whereas the mean of the recovery data was 100.3%. The proposed method has been applied to the determination of Gliclazide in commercial tablet formulations and the recovery of label claim were100.494%±0.348 for brand A and 100.111%±1.257% for brand B.  The developed method was successfully used for the assay of gliclazide. The method is simple, sensitive and precise; it can be used for the routine quality control testing of marketed formulations.DOI: http://dx.doi.org/10.3329/icpj.v1i10.11852 International Current Pharmaceutical Journal 2012, 1(10): 332-335